Chest CT scan: The best predictor of mortality in advanced pulmonary sarcoidosis? - Kirkil, Gamze; Lower, Elyse E.; Baughman, Robert P. (W B Saunders Co Ltd, 2020)
[Abstract Not Available]
Keywords: Hypertension; Survival; Features